CHANGES AND CHALLENGES IN HIGHER EDUCATION SERVICES AFTER COVID19 PANDEMIC (THE CASE OF ISRAEL & THE REPUBLIC OF MOLDOVA) - LEVKOVICH Lavan Limor (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The COVID-19 crisis that broke out all over the world in March 2020 has influenced all life areas and economy, including higher education. The transition to online distance learning in a very short time for organization, and the social and economic emergency, had significant implications on the higher education system and those who study. A quick and effective organization of higher education institutions and research institutes promoted higher education in some of the countries to the front of pedagogic competition and progress, which attracted international students and brought academic prosperity of the institutions. The transition to distance learning, which was forced due to health-social constraints, changed the higher education systems’ perception and promoted innovative ideas in placing higher education as an economicsocial factor in each country. This article, which is part of a doctoral thesis that discusses the position of higher education as a factor of competitiveness and student mobility, will try to map what was done in both countries, Israel and Moldova.